P462 Dietary restrictions on inflammatory bowel disease. (25th January 2019) - Macedo, C; Portela, F; Ferreira, A M; Lopes, S; Mendes, S; Ferreira, M; Tomé, L
Abstract: Background: Patients with inflammatory bowel disease (IBD) have symptoms associated with inflammation of the gastrointestinal tract that can lead to changes in their dietary habits to control their symptoms. The objective of this study was to demonstrate that there is an excessive food restriction in this group of patients. Methods: Prospective study evaluating the eating habits of 34 patients with IBD in the symptomatic and asymptomatic phases of the disease. Results: Of the 34 patients, 38.2% were male and 61.8% female. 73.5% had Crohn's Disease (CD) and 26.5% ulcerative colitis (UC) with a mean of 13.2 years of disease duration. The mean body mass index (BMI) was 22.8 kg/m 2 . In the symptomatic phase of the disease, 97.1% of the patients stated that they had food restrictions, avoiding 3.4 food groups, more frequent abstain of vegetables and dairy products. In the asymptomatic phase, 79.4% of the patients made restrictions, avoiding 2.2 food groups, with milk products being the most exclude. Patients with a history of small and/or large intestine removal were twice as restrictive in the symptomatic phase of the disease (7.5 food groups). Thirty per cent of patients maintained the same restrictions in the symptomatic and asymptomatic phase of the disease. Analysing the restrictions by IBD type, they were similar in both phases of the disease. Patients with a higher educational level restricted an average of one more food group in the symptomatic phase of the disease. In addition to food groups, restrictions on confection methods were observed both in the symptomatic and asymptomatic phases, being more evident in the first one, with fried being the most avoided. Conclusions: There is an excessive food restriction in both phases of the disease, although exclusion diets are not recommended and there is little evidence of their role in symptom relief. Creating a multi-disciplinary consultation of IBD with the presence of a nutritionist would bring benefits to combat myths and adjust the diet individually to avoid unnecessary restrictions that may bring future complications.